1998
DOI: 10.1200/jco.1998.16.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy and bone marrow rescue for young children with newly diagnosed malignant brain tumors.

Abstract: A significant proportion of children with malignant brain tumors can avoid radiotherapy and prolonged maintenance chemotherapy yet still achieve durable remission with this brief intensive chemotherapy regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(143 citation statements)
references
References 38 publications
3
136
0
4
Order By: Relevance
“…[22][23][24][25][26][27] In the current study, we treated 27 patients with recurrent or newly diagnosed brain tumors. This group, which was heterogeneous with respect to histologic diagnosis and disease stage at study entry, had a 23% response rate to HDCT (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27] In the current study, we treated 27 patients with recurrent or newly diagnosed brain tumors. This group, which was heterogeneous with respect to histologic diagnosis and disease stage at study entry, had a 23% response rate to HDCT (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the toxicities, complications and overall mortality and morbidity of the BCNU/thiotepa/VP-16 combination, a modified regimen without a nitrosourea, and which incorporates carboplatin in addition to thiotepa and VP-16 has been developed. 21,23,30,31 Toxicity outcome has been improved and progression-free survival appears promising.…”
Section: Discussionmentioning
confidence: 99%
“…In the Head Start I and II studies, patients received RT only if residual tumor remained at the time of HDCT/auto-SCT or if the tumor had relapsed after HDCT/auto-SCT. [11][12][13] In the present study, the use of RT was determined by the tumor status after initial surgery but not the tumor status after chemotherapy, including HDCT/auto-SCT. Therefore, 9 of 13 patients who were in CR after tandem HDCT/ auto-SCT received RT after 3 years of age according to the tumor status at the time of diagnosis (L-RT alone in 2, CSRT alone in 3, and both L-RT and CSRT in 4 patients).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Clinical trials using HDCT/auto-SCT for treatment of infants and young children with malignant brain tumors have shown that it is possible to avoid or defer RT until 3 years of age while maintaining or improving survival rates. [11][12][13] Additionally, several recent studies have suggested that dose-escalation using tandem HDCT/auto-SCT might further improve outcomes in the treatment of recurrent or high-risk brain tumors. 14,15 In the present study, we prospectively evaluated the feasibility and effectiveness of tandem HDCT/auto-SCT in children o3 years of age with malignant brain tumors.…”
Section: Introductionmentioning
confidence: 99%